THE INFLUENCE OF THE IMPLEMENTATION OF THE HARMONIZATION OF TAX REGULATION LAW ON THE ECONOMIC GROWTH OF INDONESIA - Anisa Putri Nurdian; Dian Nirmala Dewi; Eksa Ridwansyah (UNKLAB Business School, 2023)
This study aims to analyze whether there are significant differences in Indonesia's economic growth before and after the enactment of the COGS Law. The method used in this research is using SPSS tool testing parametric statistical difference test with Paired Sample T Test. Based on the calculation of descriptive statistical analysis shows that the enactment of the COGS Law has an impact on Indonesia's economic growth, namely increasing the average economic growth of Indonesia from 0.62% before the enactment of the COGS Law to 1.00% after the enactment of the COGS Law. The Paired Sample T Test results show that economic growth in the Paired Sample T Test has a Sig. (2-tailed) of 0.000 or 0.05, which means that Indonesia's Economic Growth after the enactment of the COGS Law has a significant difference. The results of this study prove that one of the objectives of the COGS Law is achieved, namely to increase growth and support the acceleration of economic recovery. Keywords: economic growth, gross domestic product, harmonization of tax regulation law Penelitian ini bertujuan untuk menganalisa apakah terdapat perbedaan pertumbuhan ekonomi Indonesia yang signifikan pada masa sebelum dan setelah pemberlakuan UU HPP. Metode yang digunakan dalam penelitian ini menggunakan alat SPSS pengujian uji beda statistik parametrik dengan Paired Sample T Test. Berdasarkan perhitungan analisis statistik deskriptif menunjukkan bahwa pemberlakuan UU HPP memiliki dampak terhadap pertumbuhan ekonomi Indonesia yaitu meningkatkan rata rata pertumbuhan ekonomi Indonesia dari yang sebelum pemberlakuan UU HPP sebesar 0,62% menjadi 1,00% setelah pemberlakuan UU HPP. Hasil uji Paired Sampel T Test menunjukkan pertumbuhan ekonomi pada uji Paired Sampel T Test memiliki hasil Sig. (2-tailed) sejumlah 0,000 atau 0.05 yang berarti Pertumbuhan Ekonomi Indonesia setelah pemberlakuan UU HPP terdapat perbedaan yang signifikan. Hasil dari penelitian ini membuktikan bahwa salah satu tujuan UU HPP tercapai yaitu untuk meningkatkan pertumbuhan dan mendukung percepatan pemulihan perekonomian. Kata kunci: pertumbuhan ekonomi, produk domestik bruto, undang undang harmonisasi peraturan perpajakan